Realitas Kemanusiaan dalam Naskah Feature “Cermin Kehidupan Pejuang Penyu” pada Buletin Pro 1 Radio Republik Indonesia Bengkulu - Pisca, Merta Edya; Yuliati; Indiarma, Verani (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
This study analyzes and describes the reality of humanity in the feature script "Mirror of the Life of Turtle Fighters" in the pro 1 bulletin RRI Bengkulu, with three discourse structures, namely macrostructure, superstructure, and microstructure. Data collection techniques use text content analysis and literature studies relevant to this study. With data analysis and processing techniques using Critical Discourse Analysis (AWK) model Teun A.van Dijk. The results of Teun van Dijk's Critical Discourse analysis found that from the elements of macrostructure, superstructure, and microstructure this feature script wants to explain a warrior's struggle regarding changes that have occurred in turtle populations in recent years that continue to decline and can cause damage to marine ecosystems, but in the feature script there is a lot of lack of information about how important sea turtles are for the sea and humans also there is no definite information What bad possibilities will happen if Extinct sea turtles.